2021
DOI: 10.3390/agronomy11030551
|View full text |Cite
|
Sign up to set email alerts
|

Crocus sativus L. Ecotypes from Mediterranean Countries: Phenological, Morpho-Productive, Qualitative and Genetic Traits

Abstract: The characterization of C. sativus ecotypes is of great interest for preserving them from a possible genetic erosion due to the decrease of European cultivation surface. In this study, we evaluated four ecotypes from Italy (Sardinia and Abruzzo), Spain (Castilla-La Mancha), and Greece (Kozani) in order to detect the existence of variability and promote the biodiversity of this crop. Thirty-one traits related to saffron flowering, flower morphology, production of spice and daughter corms, vegetative development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…It is called "the red gold" and is currently considered to be the world's most expensive spice [1,2]. Saffron has been known for four millennia and probably originated in the Middle East or in Greece (the southern Aegean islands of Crete and Santorini) [3]. Although it is principally used as a natural dye and as a flavoring in culinary preparations, several pharmacological properties, including antioxidant, antiinflammatory, antidepressant and anticancer, have been confirmed for saffron [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is called "the red gold" and is currently considered to be the world's most expensive spice [1,2]. Saffron has been known for four millennia and probably originated in the Middle East or in Greece (the southern Aegean islands of Crete and Santorini) [3]. Although it is principally used as a natural dye and as a flavoring in culinary preparations, several pharmacological properties, including antioxidant, antiinflammatory, antidepressant and anticancer, have been confirmed for saffron [3].…”
Section: Introductionmentioning
confidence: 99%
“…Saffron has been known for four millennia and probably originated in the Middle East or in Greece (the southern Aegean islands of Crete and Santorini) [3]. Although it is principally used as a natural dye and as a flavoring in culinary preparations, several pharmacological properties, including antioxidant, antiinflammatory, antidepressant and anticancer, have been confirmed for saffron [3]. In a very recent study, saffron has been also indicated as a promising anti-inflammatory and antiviral herbal medicine in the prevention of severe COVID-19 symptoms [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Saffron ( Crocus sativus L.), cinnamon ( Cinnamomum verum ), cumin ( Cuminum cyminum L.), black pepper ( Piper nigrum L.), sweet paprika ( Capsicum annuum L.), and curry belong to the group of spices most consumed all over the world. Saffron, the dried red stigma of flowers of Crocus sativus L., is mainly produced by Iran, followed by India, Afghanistan, Morocco, and Euro-Mediterranean countries including Greece, Spain, and Italy [ 6 ]. It is a highly valued spice not only for its unique aroma, taste, and color, but also because the harvesting and separation of the stigmas are done manually, being tedious and labor-intensive work.…”
Section: Introductionmentioning
confidence: 99%